Recursive Detection of M-Ary Signals over Fast Varying Mobile Communication Channel - Ahmed El-Sayed El-Mahdy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Mobile radio is characterized by a fast time varying channel. Conventional detectors which designed optimal for non-fading channel exhibit a limited performance in fast time varying channel. In this paper a recursive detector for M-ary signals over fast time varying mobile communication channel is introduced. The proposed detector continuously estimates the channel directly within the metric calculation of the log-likelihood function in a recursive manner. The estimation of the channel is performed by the covariance form of the recursive least square approach. The performance of the detector is evaluated in terms of the misdetection probability. The effects of timing and phase offsets on the performance of detector are examined by simulation. Simulation results show that the proposed detector can accommodate the fast time varying channel with adequate performance.